B‐cell‐activating factor code and human cytomegalovirus infection in renal transplant recipients. (August 2014) - Xu, Haiyan; Dong, Panpan; He, Xiaozhou; Ma, Xuyi; Xue, Dong; Zhang, Yanyun; Zhang, Xueguang
Abstract The objective of the present study was to explore the correlation between the BAFF signal and HCMV‐TLR activation in RTx recipients complicated by HCMV. Peripheral blood (anticoagulated by EDTA‐Na2) and urine of 113 RTx recipients were collected; healthy volunteers were controlled. Urine HCMV‐DNA was detected by real‐time PCR. Recipients were classified into a positive group (>10, 000 copies/mL urine) and a negative group (<10, 000 copies/mL urine). ELISA results showed that sBAFF, sera anti‐HCMV pp65 immunoglobulin (Ig)G antibody, and total IgG all significantly increased in recipients with positive HCMV‐DNA (>10, 000 copies/mL urine) (P < 0.05) compared with negative recipients (<10, 000 copies/mL urine). In the positive group, HCMV‐DNA copies and total IgG positively correlated with sBAFF (r = 0.988 and 0.625, respectively) (P < 0.05). Luminex assay results suggested that the incidence of anti‐HLA I and II and MICA antibody obviously increased in positive recipients. The expression level of BAFF and BAFF‐R increased in positive recipients. A total of 88 particular genes—involved in TLR signaling pathways, NF‐κB signaling pathways, and cytokine‐cytokine receptor signaling pathways—were detected in real‐time PCR chip assay. A total of 46 genes were differentially expressed greater than two‐fold, and the expression characteristic of BAFF‐R was concordant with FACS results. Our findings are that activation of HCMV would induce or enhance the activation of BAFF code in RTx recipients, which may independently or cooperatively participate in renal allograft injury and decrease the long‐term outcome of renal allografts.